A hybrid evaluation approach using fuzzy TOPSIS and MSGP for catering food reverse logistics provider selection in airline industry. (19th January 2023) - Fu, Yan-Kai; Liao, Chin-Nung
Reverse logistics provider selection is an important issue in catering food for airline industry. In previous research, the catering food industry generally lacked a formal reference method for reverse logistics provider's selection in catering products. The objective of this paper is to develop an integrated approach, combining techniques for order preference by similarity to ideal solution (TOPSIS) and multi-segment goal programming (MSGP) model to select reverse logistics provider. In addition, this method will guide decision makers (DMs) to evaluate reverse logistics provider by taking into account the tangible and intangible resource under catering company logistics strategic. The advantage of this approach is its consideration of both qualitative and quantitative criteria which allows DMs to set multiple segment aspiration levels for reverse logistics provider selection. A case study of application is also presented by using a catering food manufacturer.